Cuerpo, masculinidad y estilo en jóvenes de sectores altos de Lima - Villa, Julio (Pontificia Universidad Católica del Perú. Fondo Editorial, 2015)
This paper approaches masculinity through the study of the body, taking into account its aesthetics tounveil a subject not well documented and to explore the experience and representation of masculinity in a socioeconomic sector that is not well known. The research on masculinities in Latin America and the world, point out three essential components: the persistent demonstration of masculinity

the distinction between feminine and homosexual

and the control of emotions. This research shows that, in the social sector explored, the concept of masculinity widens and the three components that were pointed out before, are reduced in intensity

meanwhile we foresee the importance of the body as an individuation factor and as an esthetic innovation. Through the practice of ethnography in two independent design stores in Lima, we observe that the appearance is produced when the personal taste, the salesmen as cultural intermediaries and the feminine figure intertwine.

Esta investigación aborda la masculinidad desde el cuerpo tomando como eje de análisis la estética corporal para poder arrojar luces sobre una dimensión poco estudiada y sobre la experiencia y re- presentación de la masculinidad en un sector que falta explorar. Los trabajos sobre masculinidades en América Latina y el mundo señalan tres componentes esenciales: la demostración constante de la masculinidad, la diferenciación con lo femenino y homosexual y el control de las emociones. Este trabajo evidencia que, en el sector social explorado, las fronteras de la masculinidad se amplían y los tres componentes antes señalados se reducen en intensidad mientras que se vislumbra la importancia del cuerpo como factor de individuación e innovación estética. Realizando una etnografía en dos tiendas de diseño independiente en Lima se observa que la apariencia se produce cuando se intersecta el gusto propio, el trabajo del vendedor como intermediador cultural y la figura femenina.
Body, masculinity and style in the upper-class youth of Lima
Keywords: Masculinidad; Cuerpo; Estética Corporal; Sociology; Masculinity; Body; Body Aesthetics; https://purl.org/pe-repo/ocde/ford#5.04.00